Transforming cooking practices in Uganda: transitioning toward clean energy solutions - Elasu, Joseph; Ntayi, Joseph M.; Orobia, Laura A.; Adaramola, Muyiwa S.; Onyinyi, Bernard (Frontiers in Sustainability, 2025)
Cooking in Uganda is deeply rooted in cultural traditions, influencing the choice of cooking solutions across different regions. This study aims to map clean cooking practices, identify key interventions, and highlight challenges hindering their widespread adoption and sustained use. A systematic literature review, guided by the PRISMA approach, was employed to ensure a rigorous and transparent selection of scholarly sources. Findings reveal that traditional biomass, mainly firewood and charcoal, continues to dominate Uganda’s cooking landscape, while modern alternatives like LPG, ethanol, and electric cooking remain underutilized due to cultural preferences, affordability constraints, and infrastructure limitations. To address these challenges, the study recommends targeted subsidies, Pay-As-You-Go financing models, and tax exemptions to reduce initial costs. Additionally, regulatory interventions should stabilize fuel prices, expand fuel distribution networks, and invest in rural electrification via solar mini-grids. Integrating electric cooking into Uganda’s broader renewable energy and climate policies would further support widespread adoption and contribute to sustainability goals.